Improving Relay Running Learning Outcomes through the Cooperative Learning Method of the Team Accelerated Instruction Model among Sixth Grade Students at SD 017137 Mekar Sari Asahan - Manurung, Rido; Sari, Liliana Puspa; Nugroho, Agung (Educational Sciences Journal, 2025)
This study aimed to determine the improvement of relay running learning outcomes through the Team Accelerated Instruction (TAI) cooperative learning model for sixth-grade students at SD 017137 Mekar Sari Asahan in the 2023/2024 academic year. Theoretically, this model emphasizes teamwork, individual accountability, and collaborative learning to enhance psychomotor skills and mastery of physical techniques. The research employed a Classroom Action Research (CAR) approach based on the Kemmis and Taggart spiral model, consisting of planning, acting, observing, and reflecting stages. The study involved 18 students as research subjects, using an observation rubric to assess relay running techniques, including starting, baton exchange, and finishing skills. The results showed that only 27.8% of students achieved mastery in the pre-test, with an average score of 57. After applying the TAI model in cycle I, 44.4% of students achieved mastery with an average score of 70. In cycle II, the number increased to 83.3% with an average score of 78, meeting the classical mastery criterion of 80% (minimum score 75). These findings indicate that the TAI model effectively improved students’ relay running performance by promoting cooperative interaction, technical skill enhancement, and active participation.